Influence Of Servant Leadership, Organizational Safety Culture And Work Environment On Organizational Citizenship Behavior In Application Of Patient Safety With Affective Organizational Commitment - Ana Faizah; Jemmy Rumengan; Nurhatisyah nurhatisyah; Sri Yanti; Nolla Puspita Dewi (IAIC Publishing, 2021)
The success of the application of patient safety in hospitals, among others, is measured by how much the productivity of nurses in providing quality nursing care to patients and their families. Factors that influence patient safety: organization (safety culture), work environment, individual factors and citizenship behavior, work behavior, teamwork structure and (servant) leadership. In this regard, the purpose of this literature review study is to prove the influence of servant leadership, organizational safety culture and work environment on OCB in the application of patient safety with affective organizational commitment in hospital. This literature review is based on literature sources and related scientific research journals. The method used in this paper is to search from the EBSCO, ProQuest, and Google Scholar databases using keywords servant leadership, organizational safety culture, work environment, OCB, and patient safety. The study population was health workers in the hospital, which measures in the construction are 54 respondents, with a random sampling technique as the sample of the population. The data were analyzed using parametric and non-parametric statistics with SEM-PLS (Structural Equation Modeling-Partial Least Square). The research proves that: Servant leaders and organizational safety culture that is applied, as well as a supportive work environment, have a positive influence on OCB in the application of patient safety in hospitals. Furthermore, it is expected that nurse managers will be able to implement servant leadership and safety culture as well as adequate work environment support so that OCB in implementing patient safety can run optimally, this can be assessed based on patient safety incidents and service quality as hospital brand equity.